Avian Pathogenic Escherichia coli and Clostridium perfringens: Challenges in No Antibiotics Ever Broiler Production and Potential Solutions - Fancher, Courtney A. (Microorganisms, 2020)
United States is the largest producer and the second largest exporter of broiler meat in the world. In the US, broiler production is largely converting to antibiotic-free programs which has caused an increase in morbidity and mortality within broiler farms. Escherichia coli and Clostridium perfringens are two important pathogenic bacteria readily found in the broiler environment and result in annual billion-dollar losses from colibacillosis, gangrenous dermatitis, and necrotic enteritis. The broiler industry is in search of non-antibiotic alternatives including novel vaccines, prebiotics, probiotics, and housing management strategies to mitigate production losses due to these diseases. This review provides an overview of the broiler industry and antibiotic free production, current challenges, and emerging research on antibiotic alternatives to reduce pathogenic microbial presence and improve bird health.